Desenvolvimento de um modelo animal para avaliação da eficiência de vacinas contra gangrena gasosa causada por Clostridium perfringens tipo A - Jose Azael Zambrano Uribe (2013)
The myonecroses infections caused by Clostridium perfringens type A are characterized by rapid course and high mortality, not knowing the impact it has on both national and global livestock. The objective of the present work was to establish a model of experimental induction of gas gangrene by inoculation of vegetative bacteria Clostridium perfringens type A, as well as to assess the efficacy of three experimental vaccines (toxoid, bacterin, toxoid + bacterin) and another of commercial source. Were used 98 albino guinea pigs (Cavia porcellus) of the lineage "Inglês short ear", males, weighing between 300 and 500 grams. Of these total, 50 were used to establish the dose of challenge and 48 for assessing the effectiveness of vaccines. For experimental reproduction of myonecrosis in guinea pigs and the production of the bacterin and toxoid were used a reference sample of the American Type Culturet colecction2 of Clostridium perfringens type A (ATCC 13124) belonging to the Anaerobic Laboratory EV -UFMG. The totality of guinea pigs (48) was divided into six groups. Were administer one ml of the immunogen subcutaneously or placebo on day zero and, at day 21 after primary vaccination, all groups were boosted or received placebo again. The animals were challenged by inoculating 107 CFU/mL vegetative bacteria Clostridium perfringens type A intramuscularly. All animals were clinically evaluated two hours before inoculation and every two hours after this until 72 hours after the challenge. The assessment was made at times considered most important, with a total of seven observations. Subsequently, all animals were euthanized and necropsied immediately after to evaluate the changes. The clinical and autopsy parameters were defined by parameter and total score. When comparing the maximum clinical scores of the groups, it was determined that the Bacterin + Toxoid group (10.80) showed the best behavior, not finding a statistical difference when compared with the Negative Control group, followed by Toxoid group (13.13) and Commercial toxoid (13.25), with minor signs of illness. The Bacterin group was considered as inefficient, with the highest total score of the evaluated clinical vaccines (28.71), finding no statistical difference when compared with the Positive Control group. These results were also observed in the total score autopsy, with the best results being in Bacterin + Toxoid group (12.8), followed by Toxoid group (16.25), Commercial Toxoid (15.38), Bacterin (27.14), Negative Control (10.00) and positive control (29.57). In conclusion, the best immunization protocol was Bacterin + Toxoid. It is possible to assess the effectiveness of vaccines using this model and could be used as a standard for evaluating vaccines against Clostridium perfringens type A and other histotoxics clostridia that causes myonecrosis.